Study of thyroid function in patients admitted in intensive care unit in a tertiary care centre - Sasi Sekhar, T. V. D.; Appalaneni, Ramya; Jada, Avinash; Pinnamaneni, Shalima (International Journal of Research in Medical Sciences, 2018)
Background: Thyroid hormones play a key role in the maintenance of body growth by modulating metabolism and the immune system. These alterations in thyroid hormone levels are referred to as “euthyroid sick syndrome” or “non thyroidal illness syndrome” (NTIS), which is characterized by low serum levels of free and total triiodothyronine (T3) and high levels of reverse T3 (rT3) accompanied by normal or low levels of thyroxine (T4) and thyroid-stimulating hormone (TSH). During critical illness, changes in circulating hormone levels are a common phenomenon. These alterations are correlated with the severity of morbidity and the outcomes of patients in ICU. Methods: This study was carried out at a tertiary care hospital. 100 patients of age above 18yrs, both sexes, admitted to intensive care units with following diseases Septicemia, ARF, Respiratory failure, CCF, DKA, Stroke were taken into the cross-sectional study. Relevant hematological and radiological examination are done. Fasting venous blood samples were collected immediately on admission to ICU from all patients and were subjected for hormone analyses. Samples were tested for total T3, total T4, and TSH. The hormone estimation was done by chemiluminescence assay. Results: Patients (59%) had low T3 level, 41(41%) patients had normal T3, 31 patients (31%) had low T4, 69 patients (69%) had normal T4 level and TSH was low in 11 patients (11%), 76 patients (76%) had normal TSH and 14 patients (14%) slightly high. Our study showed low T3 (59%) is the commonest abnormality in ICU admitted patients. There is a significant relation present between T3 and mortality (p value-0.0001) and need for ventilation (p value 0.004). Conclusions: Our study suggests that low T3 is an important marker of mortality in ICU admitted patients. We suggest that in ICU patients T3 levels should be done and used as a prognostic marker for mortality and need for ventilation.